FRI0719 Burden of hepatitis e virus infection in patients with rheumatic diseases. (15th June 2017) - Jacques, P; Padalko, E; Verheugen, E; Cattoir, L; Verhelst, X; Nys, E; Gucht, S Van; Hutse, V; Suin, V; Elewaut, D
Abstract : Background: Hepatitis E virus (HEV) is considered an emerging pathogen in developed countries, potentially causing chronic hepatitis. Objectives: This cross-sectional analysis was undertaken to determine the seroprevalence of HEV in patients with autoimmune or inflammatory arthritis. This subgroup of patients is often treated with immune suppressive drugs, and is generally considered more susceptible to infections. Methods: Serum samples were obtained from 449 consecutive patients consulting at the department of Rheumatology between October and November 2015. Patient characteristics with respect to diagnosis and treatment were collected. HEV IgM and IgG were measured by ELISA (Wantai Hepatitis E Virus IgG and IgM ELISA, Sanbio BV). Positive or borderline samples were further analyzed for HEV RNA (RealStar® HEV RT-PCR Kit, Altona Diagnostics NRC WIV). Results: A total of 449 patients were included, 211 men and 238 women. HEV IgG was positive in 82 samples (18.26%), 6 were borderline, and 5 were non-determinable (not enough serum). IgM was positive in only 2 samples (0.45%). These 2 patients had normal liver function tests. Additional PCR was performed on all positive and borderline samples, which turned out negative in all samples. Of the 88 IgG positive and borderline samples, 86 patients had a known diagnosis of chronic inflammatory arthritis, of which 50 patients had previously been diagnosed with rheumatoid arthritis, 18 with spondyloarthritis, 8 with psoriatic arthritis. Fifty patients were treated with biologics (37 TNF inhibitors), 43 patients were treated with methotrexate (mean dose 12.5mg weekly), and 20 were treated with corticosteroids (mean daily dose 5.5mg prednisolone equivalent). Conclusions: In a consecutive cohort of patients with known diagnosis of autoimmune or inflammatory arthritis, seroprevalence of HEV IgG was 18, 2%. No active HEV infection could be detected. We found this to be comparable to a historical cohort of healthy patients from the departments of Orthopedics and obstetrics 1, where prevalence of HEV IgG was 14%. References: Van Hoecke F et al. Acta Gastroenterol Belg. 2012 Sep;75(3):322–4. Disclosure of Interest: None declared